Boundary-induced bulk phase transition and violation of Fick's law in two-component single-file diffusion with open boundaries - Brzank, Andreas; Schütz, Gunter M. (Diffusion Fundamentals, 2006)
We study two-component single-file diffusion inside a narrow channel that at its ends is open and connected with particle reservoirs. Using a two-species version of the symmetric simple exclusion process as a model, we propose a hydrodynamic description of the coarse-grained dynamics with a self-diffusion coeffcient that is inversely proportional to the length of the channel. The theory predicts an unexpected nonequilibrium phase transition for the bulk particle density as the external total density gradient between the reservoirs is varied. The individual particle currents do not in general satisfy Fick''s first law. These results are confirmed by extensive dynamical Monte-Carlo simulations for equal diffusivities of the two components.